O aluno surdo no ensino médio da escola pública: o professor fluente em libras atuando como intérprete - Pedroso, Cristina Cinto Araújo [UNESP] (2006)
The school nowadays makes an effort to meet the ideals of educational inclusion, which foresees its reorganization to guarantee an effective educational process of its students independent of their necessities and particularities. Concerning deaf people, a school of quality is one that is able to both provide to this student the ideal conditions of learning and leading him to get involved academically and socially, so that old discriminatory excluding paradigms based on oralism and total communication can be overcome, providing teaching sign language, the adequate teaching procedures, a bilingual and bicultural curriculum, teachers with special training, the educational interpreter, the assistance of deaf sign language professionals, the interlocution among the deaf and hearing students and, finally, a comprehensive school reorganization. Therefore, deaf education has been based on the interface between the presuppositions of educational inclusion and bilingualism. Based on this data, this research aimed to demonstrate and analyze the opinion of the teachers, colleagues and managers concerning the performance of a fluent LIBRAS's teacher as an interpreter, in an ordinary high school class group. The data were obtained by interviewing five teachers, six hearing students, the vice director and the coordinator. Besides, notes were taken about the educational activities developed in the classroom and also about the relationship among the deaf students, the teachers and hearing students. It could also be noticed that the fluent LIBRAS's teacher, performing as an interpreter, assumes teacher's role, while the school doesn't. The attitudes taken by the interpreter go beyond a simple interpretation. Besides, it was noticed that the teachers blame themselves for the limits of the deaf students and they haven't realized the political dimension of this inclusion. Based on the... (Complete abstract, click electronic access below)